A matrix decomposition MFS algorithm for certain linear elasticity problems - Karageorghis, A.; Smyrlis, Y. -S.; Tsangaris, T. (Numerical algorithms, 2006)
We propose an efficient matrix decomposition Method of Fundamental Solutions algorithm for the solution of certain two-dimensional linear elasticity problems. In particular, we consider the solution of the Cauchy–Navier equations in circular domains subject to Dirichlet boundary conditions, that is when the displacements are prescribed on the boundary. The proposed algorithm is extended to the case of annular domains. Numerical experiments for both types of problems are presented.